PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI PENERAPAN MODEL PEMBELAJARAN LANGSUNG DI KELAS V SDIT AL-JAUHAR KECAMATAN MANDAU - Asri Febriyona; Syofni Syofni; Japet Ginting (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This research aims to improve the learning process and improve learning outcomes the fifth grade of mathematics students at Al-Jauhar Mandau by applying the direct instructional model. The subject of the research were students of class V. This research is a class act with two cycles. Each cycle has four stages, the stages are planning, implementation, observation and reflection. To get the results, do analysis data of the teachers and students activitieswith the observation sheets and the analysis data ofmathematicslearning outcomesof studentsfrom the test in every in the end of the cycle. The improvements of the learning process of the students and the increase in the numberof studentswho achievedatUHKKM in the endof eachcyclecompared to thenumber ofstudents who achieveda score ofKKMonthe basis score. The result of the researchshowsthatthroughthe application ofdirectinstructional modelcan improve the learning outcomes of mathematics studentsin fifth grade at SDIT Al-Jauhar Mandau in the first semester of academic year 2013/2014.Keywords: Mathematics Learning Outcomes, Learning Direct, Classroom Action Research.